The offensive efficiency of the high-level handball players of the front and the rear lines - Moncef, C.; Dagbaji, G.; Abdallah, A.; Mohamed, S. (Asian Journal of Sports Medicine, 2011)
Purpose: The aim of this study was to investigat the offensive efficiency of the professional handball players forming the front and rear lines. Methods: Our investigation was carried out on four matches (final, semi-finals and classifying match) at the 19th male Handball World Championship "Tunisia 2005". Finalist teams were Tunisia, France, Croatia, and Spain. Matches were recorded using 5 digital camcorders (SONY, DCL, and TRV 130E). Number of passes and the length of the attacks were determined by software "STUDIO 9". Speed of the ball at the different shootings was calculated by REGAVI software, version 2.57, 2004. Work was dissociated according to 2 variables namely axes and lines. Results: Players of lateral axes (A4) and front basis (L1) were shorter and thinner than those of the central axis (A3) and rear basis (L2). No differences were observed between lines and axes in age. The analysis of the total shootings to the goal shows that the players of lines and axes present very close values in each team, excepting the Croatian L2 compared to the Tunisian L2. Players of the rear Croatian basis present also a number of attacks concluded by a non-successfully cadred shooting greater than all other groups. In the Spanish group, a significant difference among number of passes concluded by a non-successfully cadred shooting between lines, and front basis vs central axis was noted. No significant difference was found between lines and axes in the Croatian team. Regarding the velocity of shooting, excepting the Croatian team, no differences were found between lines and axes of the other teams. No differences were also noted in the attack duration between lines and axes in Croatian and Tunisian teams. In the Spanish team, duration of attacks concluded by a cadred shooting was most important when finished by an L2 or an A3 player. Conclusion: The present results demonstrate that finalist teams were found to be clearly characterized by L2 and A3 players taller and weightier than those of L1 and A4. Organized attack was generally concluded by shooting done by an L2 or an A4 player and the shooting velocity did not significantly determine the offensive efficiency.